In vivo investigation of temporomandibular joint regeneration: development of a mouse model. Issue 7 (July 2020) - Hakim, M.A.; Guastaldi, F.P.S.; Liapaki, A.; Ahn, D.Y.; Mueller, M.-L.; Troulis, M.J.; McCain, J.P.
Abstract: Temporomandibular joint (TMJ) reconstruction is traditionally invasive. Several investigators have developed animal models, including mouse models, to study the TMJ. However, there are no detailed descriptions of a mouse model to be followed for additional research. The goal of this project was to study minimally invasive TMJ regeneration using tissue engineering in mice. As part of the project, a detailed mouse model was developed, which is described in this article. Eight carcasses were used to study the anatomy of the TMJ of the mouse and 36 mice were used to describe the surgical approach and perioperative management. The study showed similarities and differences when compared to humans. One mouse died suddenly 10 days postoperatively, while 35 mice survived the operation. Keratitis and wound dehiscence were the most common complications. Investigators reviewing this paper should be able to use this mouse model to further study TMJ regeneration in mice.